2020
DOI: 10.1123/ijspp.2019-0616
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Self-Reported Physical Fitness, Performance, and Side Effects Across the Phases of the Menstrual Cycle Among Competitive Endurance Athletes

Abstract: Purpose: To investigate changes in self-reported physical fitness, performance, and side effects across the menstrual cycle (MC) phases among competitive endurance athletes and to describe their knowledge and communication with coaches about the MC. Methods: The responses of 140 participants (older than 18 y) competing in biathlon or cross-country skiing at the (inter)national level were analyzed. Data were collected via an online questionnaire addressing participants’ competitive level, training volume, MC hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
79
6
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(152 citation statements)
references
References 33 publications
21
79
6
3
Order By: Relevance
“…While these athletes are considered to be playing at the top-level of competition for their sport, given the infancy of these competitions, little research is available on these athletes to inform athlete management practices. Additionally, most research regarding the menstrual cycle and hormonal contraceptive use to date has been conducted on the general population (Schaumberg et al, 2018;Mackay et al, 2019;Freemas et al, 2020) or endurance athletes (Redman and Weatherby, 2004;Solli et al, 2020). Further research is therefore necessary to report the prevalence and reasons for HC use within female football codes to help shape athletes' management and monitoring practices.…”
Section: Introductionmentioning
confidence: 99%
“…While these athletes are considered to be playing at the top-level of competition for their sport, given the infancy of these competitions, little research is available on these athletes to inform athlete management practices. Additionally, most research regarding the menstrual cycle and hormonal contraceptive use to date has been conducted on the general population (Schaumberg et al, 2018;Mackay et al, 2019;Freemas et al, 2020) or endurance athletes (Redman and Weatherby, 2004;Solli et al, 2020). Further research is therefore necessary to report the prevalence and reasons for HC use within female football codes to help shape athletes' management and monitoring practices.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies that did observe a MC effect to performance, there were inconsistencies in findings but strength and aerobic performance were most commonly reported to be impaired during the late luteal phase, and anaerobic performance was most frequently reduced in the late follicular phase. With regards to perceived performance, the late luteal phase was also one of the phases athletes perceived their performance declined [ 75 , 76 ]. The research that finds the MC does have a mediating role in physical performance shows that MC phases affect strength, aerobic and anaerobic performance differently.…”
Section: Discussionmentioning
confidence: 99%
“…It is apparent that many athletes believe their performance fluctuates with MC phase; indeed, all included studies reported that MC phase impacted athletes’ perceived performance [ 72 , 73 , 74 , 75 , 76 ]. A large proportion, 50–71% and 49–65%, of participants reported feeling their performance in training and competition, respectively, is impaired in certain MC phases [ 72 , 74 , 76 ]. Perceived strength, speed and power ratings were also altered during certain MC phases [ 75 ].…”
Section: The Impact Of Menstrual Cycle Phase On Perceived Performamentioning
confidence: 99%
See 2 more Smart Citations